Love in a global village : a celebration of intercultural families in the Midwest - Grearson, Jessie Carroll (University of Iowa Press, 2001)
In praise of diversity, Jessie Grearson and Lauren Smith offer Love in a Global Village: A Celebration of Intercultural Families in the Midwest, an account of the triumphs of fifteen intercultural families and the perseverance of their relationships in midwestern America. The couples recount their courtships, their adventures and difficulties, and their individual choices to create families and build lives together despite differences of race, language, religion, and culture.